2017
DOI: 10.1007/s40618-017-0730-y
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome proliferator-activated receptor gamma expression in peripheral blood mononuclear cells and angiopoietin-like protein 4 levels in obese children and adolescents

Abstract: PPARγ is decreased in childhood obesity and may be responsible for diminished ANGPTL4 levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 56 publications
1
16
0
1
Order By: Relevance
“…Only one study focused on the pediatric age group has shown that circulating ANGPTL-4 levels are significantly lower in children and adolescents with obesity and positively correlated with peroxisome proliferator-activated receptor expression in peripheral blood mononuclear cells [32]. Accordingly, the present work shows a decrease in ANGPTL-4 levels in children and adolescents with obesity independent of the gender and pubertal stage.…”
Section: Discussionsupporting
confidence: 55%
“…Only one study focused on the pediatric age group has shown that circulating ANGPTL-4 levels are significantly lower in children and adolescents with obesity and positively correlated with peroxisome proliferator-activated receptor expression in peripheral blood mononuclear cells [32]. Accordingly, the present work shows a decrease in ANGPTL-4 levels in children and adolescents with obesity independent of the gender and pubertal stage.…”
Section: Discussionsupporting
confidence: 55%
“…Likewise, studies on mice with induced obesity, exhibited reduced expression of PPARα and carnitine palmitoyltransferase I (CPT-1) in the liver [ 38 ]. PPARγ expression is also reduced in PBMC from obese children and adolescents [ 39 ]. Indeed, obese mice treated with bezafibrate (BZ), an agonist that preferentially activates PPARα and PPARγ, improves biochemical parameters and reduce the WAT proinflammatory state in obese mice [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…PPAR gene is the one of the PPARs subtypes that is by far the most widely studied. It is not only the target molecular of Thiazolane diketones but also an important regulatory factor of adipocyte differentiation and fat endocrine functions of the important regulatory factor [5]. Moreover, PPAR gene acted as a signal transfer regulator between gene expression of adipocytes and adipogenesis and insulin-producing cells.…”
Section: Introductionmentioning
confidence: 99%